Investigating Seasonal Variations of Soil Thermal Properties (STPs) Under Different Land Use Patterns in Abeokuta, Southwest Nigeria - Saheed Adekunle Gainiyu; Oluwafemi Ayomide Shobowale; Yaya Korede Sikiru (JURNAL GEOCELEBES, 2022)
Soil thermal properties (STPs) command the storage and transfer of thermal energy through the soil matrix, which can be changed by land use systems and seasonal changes. Depiction of STPs based on land uses and seasonal changes eases better understanding of trend of periodic disparity of soil heat flux across varied land use practices. This study assesses the seasonal and land use prompted variability of STPs such as thermal conductivity (λs), thermal resistivity (TR), specific heat capacity (Cs), thermal diffusivity (TD) and temperature of sandy loam topsoils under different land uses: Dumpsite (DS), block-making site (BMS), abattoir site (ABS), and grassland (GL). Seasonal changeability of the STPs was determined by two reiterations of aforementioned STPs measurements during the wet (April/May, 2019) and dry (January/February, 2020) seasons. The STPs were measured in situ utilizing KD2 Pro Thermal Analyzer. The research discloses that STPs are impacted by land use substantially. All the observed STPs were not differ significantly among the studied land uses during the wet season. However, statistically substantial variations in Cs and TD of topsoils under all investigated land uses were recognized during the dry season. Moreover, no significant alteration in the mean soil temperature was observed among the sampling land uses during the dry season. The result of the present study inspires more studying the seasonal changeability of STPs based on a more agricultural and economically related land uses as well as broad sampling design to account for their spatial changeability. The findings of this study will assist land users to make best choice of appropriate land management practices for viable agriculture and environmental management.